The Effects of Sodium Citrate and an Excess of Plasminogen on Fibrinolytic Agents - Astrup, Tage; Sterndorff, Ida (Thrombosis and Haemostasis, 1960)
1. The presence of citrate in the normal fibrin enhanced the fibrinolytic activity of plasminogen activators, including trypsin. The effect of proteases (on normal or on heated fibrin, containing citrate) was not significantly influenced.2. The effect of plasminogen activators was also increased when excess of plasminogen was present in the normal fibrin plates.3. Fumaric acid and maleic acid belong to the polycarboxylic acids producing an enhancing effect.